Synthetic and Mechanistic Studies on 2,3-Dihydrobenzo[b][1,4]-oxaselenines Formation from Selenocyanates - Chao, María N.; Szajnman, Sergio H.; Cattaneo, Mauricio; Sanchez Gonzalez, Jonathan; Bonesi, Sergio M.; Rodriguez, Juan B. (Synthesis, 2020)
An expedient preparation of selenium-containing heterocycles via an m-chloroperbenzoic acid-mediated seleno-annulation starting from selenocyanate derivatives is described. In spite of its significance, this cyclization reaction is virtually understudied not only from the point of view of its scope, but also from the mechanistic aspects associated to this remarkable transformation. In this sense, several selenocyanate and thiocyanate derivatives bearing an aromatic ring were evaluated as substrates under different reaction conditions of this interesting cyclization yielding important insights on its scope as well as relevant information on the reaction mechanism.
Keywords: oxaselenines; selenocyanates; heterocycles; radical mechanism; electron transfer reaction